2022
DOI: 10.1098/rsos.190814
|View full text |Cite
|
Sign up to set email alerts
|

Is depression associated with reduced optimistic belief updating?

Abstract: When asked to evaluate their probability of experiencing a negative life event, healthy individuals update their beliefs more following good news than bad. This is referred to as optimistic belief updating. By contrast, individuals with depression update their beliefs by a similar amount, showing reduced optimism. We conducted the first independent replication of this effect and extended this work to examine whether reduced optimistic belief updating in depression also occurs for positive life events. Replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 60 publications
(86 reference statements)
1
8
0
Order By: Relevance
“…In the educational context, previous studies confirmed stronger expectation maintenance after receiving unexpected negative feedback . Unexpected positive feedback, on the other hand, was not related to stronger expectation update Hobbs et al, 2022). Our results supported the assumption that expectations tend to persist after receiving unexpected negative feedback.…”
Section: Is There An Optimism Bias In Coping With Violated Academic E...supporting
confidence: 85%
“…In the educational context, previous studies confirmed stronger expectation maintenance after receiving unexpected negative feedback . Unexpected positive feedback, on the other hand, was not related to stronger expectation update Hobbs et al, 2022). Our results supported the assumption that expectations tend to persist after receiving unexpected negative feedback.…”
Section: Is There An Optimism Bias In Coping With Violated Academic E...supporting
confidence: 85%
“…Based on previous studies and the following assumptions, we proposed that PsyCap functions as an important mediator. Women with higher self-efficacy may have more confidence to cope with risk during the pregnancy [ 29 ]; hope may contribute to a woman’s positive expectancy toward the fetus and their own health and have less focus on negative effects related to older age [ 30 ]; women with optimistic views may have positive attributions to pregnancy outcomes and deflect responsibility for negative events through an optimistic explanation [ 31 ]; when facing stressors during pregnancy, women with resilience may bounce back to normal life more quickly [ 19 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…These ndings suggest that the neuroplastic changes induced by tACS may be consolidated during the post-stimulation o ine period. Additionally, the potential of 40 Hz tACS to alter a pessimism mindset, opens avenues for therapeutic applications, particularly for individuals with depression or those who show de cits in optimistic processing (Hobbs et al, 2022;Korn et al, 2014). Therefore, to validate these ndings and understand their clinical relevance, future studies are encouraged to assess the e cacy of 40 Hz-tACS in depressed populations, thereby bridging the gap between experimental results and therapeutic potential.…”
Section: Discussionmentioning
confidence: 99%
“…The optimism bias emerges due to the preferential encoding and consolidation of desirable over undesirable information (Garrett et al, 2018;Kuzmanovic et al, 2016Kuzmanovic et al, , 2018Sharot et al, 2012;Yao et al, 2021), a process that likely involves frontal brain regions such as the anterior cingulate cortex (ACC) and inferior frontal gyrus (Sharot et al, 2011). Optimism bias plays a crucial role in mental health, with its absence potentially leading to psychiatric disorders like depression, characterized by a reduced inclination to process positive future outcomes (Hobbs et al, 2022;Korn et al, 2014). This link highlights the potential value of cognitive interventions aimed at enhancing optimism bias (Kube, 2023).…”
Section: Introductionmentioning
confidence: 99%